Dimensões comunicacionais [possíveis] nos cursos de bacharelado em comunicação organizacional brasileiros - Falavigna, Francielle Benett (2023)
The research object of our thesis are the Brazilian Bachelor of Organizational Communication courses offered by the Federal Technological University of Paraná (UTFPR) and the University of Brasília (UNB). We aim to understand the [possible] communicational dimensions promoted by the curricular experiences of these two Brazilian courses; to investigate, through their discursive productions, how Brazilian Organizational Communication courses understand/comprehend organizational communication; and, discuss the materialization of occurrences (or not) of discursive intention relations that legitimize the construction of the “I” as a collective (and professional) subject. To meet these objectives, we resorted to the Complexity Paradigm (MORIN, 2000, 2006, 2009, 2011, 2015), to Wolton (2010), to Marcondes Filho (2008) and to Buber's (2001) conceptions of communication and dialogue, to elements of the philosophy of language of the Bakhtin Circle (VOLÓCHINOV, 2018; BAKHTIN, 2011, 2014, 2015, 2016, 2019), to the relationship between education and complexity assumed by Morin (2013), to the concept of curriculum as a biopolitical device defended by Foucault (2014) and Silva (2001), for whom curricula are anchored in multiple discourses in which subjects are inserted and to what we call the 'state of the art' of technological communication courses in Brazil, whose institutionalization predates the creation of Bachelor of Organizational Communication courses. Considering the analytical dimensions based on Volóchinov (2018) and Bakhtin (2011, 2014, 2015, 2016, 2019), we identified that the syllabi of the disciplines analyzed, of the two courses that constitute the object of this research, seem to (re)problematize knowledge, contextualizing knowledge in a contemporary and responsive perspective. Likewise, we observed, as a point of attention, the non-problematization of the predominance of a instrumental communication in the final papers.